Use of the submental vessels for free gracilis muscle transfer for smile reanimation. Issue 10 (24th June 2016) - Goyal, Neerav; Jowett, Nathan; Dwojak, Sunshine; Cunane, Mary Beth; Zander, David; Hadlock, Tessa A.; Emerick, Kevin S.
Abstract: Background: Free muscle transfer is an important in dynamic facial reanimation; however, suitable donor vessels in this population can be inadequate. In this case series, the submental vessels were used as donors to free gracilis muscle in vessel‐depleted patients. Methods: Five patients underwent free gracilis muscle transfer for smile reanimation, 2 with a prior failed free gracilis transfer, 2 with vascular anomalies, and 1 with previous distal ligation of the facial vessels. The submental artery was used as a donor in all cases, and the submental vein was used in 3 cases. Results: There were no complications or flap failure. Postoperative arterial and venous blood flow was confirmed in all patients using Doppler color flow imaging above and below the anastomoses. Conclusion: The submental vessels are suitable for microvascular anastomosis for free flaps having short pedicles, such as the free gracilis muscle flap, in the vessel‐depleted hemiface. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–E2503, 2016